SYNTHESIS AND BIOLOGICAL SCREENING OF 3D TRANSITION METAL COMPLEXES WITH SCHIFF BASE DERIVED FROM 4-CHLORO BENZALDEHYDE WITH 2 AMINO 4-PHENYL THIAZOLE - NIRANJAN LAL; RAJESH KUMAR; RACHANA (International Journal of Pharma and Bio Sciences, 2015)
Metal complexes of Co (II), Ni (II), Mn (II) and Zn (II) having general formulae [ML2X2] was prepared. Where L2 = Schiff base derived from 4-chloro benzylidene with 2-amino 4- henyl thiazole. The characterization of ligand as well as their metal complexes has been made on the basis of elemental analysis, magnetic susceptibility measurement, Infrared spectra and magnetic moment data. The anti-microbial screening was done on E.Coli, S.aureus, B.subtilis, S.typhi A.niger and percentage inhibition was found after 168 hours.